Impacts of the 2022 war in Ukraine on the travel habits of Ukrainian tourists - Vito Bobek; Gal Gotal; Tatjana Horvat (Naše gospodarstvo / Our Economy, 2023)
The purpose of this paper is to explore how the travel habits of Ukrainian tourists changed after the beginning of the 2022 war in Ukraine in comparison to the year 2021. The theoretical part of the paper discusses the impacts of war on tourism; in the empirical part, the secondary and the primary research on the Ukrainians' travel habits before and during the war is performed. The research gives an insight into the frequency of travelling, planned spending on travel, ethnic dilemmas on travelling, and travel destinations. The research is essential in the context of war and post-war periods for understanding the psychological and behavioral effects, assessing economic consequences, addressing destination marketing and recovery efforts, and facilitating reconciliation and social integration. Research limitations include the scope and generalizability of the findings, self-reporting biases, causality and temporal issues, and limited timeframe and context.
Keywords: F51; O52; Z39; 330; Tourism; Travel; Travel habits; War; Ukraine